GAMBARAN EFEK SAMPING KEMOTERAPI BERBASIS ANTRASIKLIN PADA PASIEN KANKER PAYUDARA DI RSUD DOKTER SOEDARSO PONTIANAK - ., Citra Tri Wahyumi Faisel (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Breast cancer is main problem of womens health in the world. One of therapy in breast cancer is anthracycline-based chemotherapy. Chemotherapy drugs also affect normal cells that may lead to side effects.Objective : To collect data about frequently side effects of anthracycline-based chemotherapy in breast cancer patients in Soedarso General Hospital Pontianak, onset of side effect, recovery from side effect and hair changes after chemotherapy.Method: A kind of descriptive research with cross sectional design. The data was fetched by interview breast cancer patients who completed chemotherapy.Result: There were 101 patients included as samples of this research. The most frequently side effect was alopecia (94,1%). Side effects which have onset during the course of treatment to 3 days later were nausea (100%), vomiting (100%), diarrhea (80%), infected (61,5%), neuropathy (50%) and myalgias (90%); >1 week later were stomatitis (41,7%) and thrombocytopenia (100%); >3 weeks later was alopecia (45,8%). Time to recover within <1 week for nausea (74,4%), vomiting (70%), diarrhea (90%), stomatitis (75%), infected (76,9%), thrombocytopenia (57,1%) and myalgias (60%); >2-6 months for alopecia (89,6%); >6 months for neuropathy (93,8%). After chemotherapy, hair become curly (78,4%), darker (82,4%) and thicker (90,2%).Conclusion: The most frequently side effect of anthracycline-based chemotherapy was alopecia. Each side effect was varied in onset and recovery.Keywords: anthracycline-based chemotherapy onset of side effects recovery hair changes.